Absolute spectral modelling of asteroid (4) Vesta. Issue 2 (22nd November 2018) - Martikainen, Julia; Penttilä, Antti; Gritsevich, Maria; Videen, Gorden; Muinonen, Karri
ABSTRACT: We present a new physics-based approach to model the absolute reflectance spectra of asteroid (4) Vesta. The spectral models are derived by utilizing a ray-optics code that simulates light scattering by particles large compared to the wavelength of the incident light. In the light of the spectral data obtained by the Dawn spacecraft, we use howardite powder to model Vesta's surface regolith and its particle size distribution for 10–200 $μ$ m sized particles. Our results show that the modelled spectrum mimics well the observations. The best match was found using a power-law particle size distribution with an index 3.2. This suggests that Vesta's regolith is dominated by howardite particles <25 $μ$ m in size.